Meeting of Religions: New Orientations and Perspectives, - Podgors, Frank R. (Journal of Dharma, 1979)
A new spirit is alive in Asia; scholarship, spirituality, and youthful vigour are its characteristics. Although strongest in India, this spirit is not without advocates in Sri Lanka, Thailand, South-East, and even East Asia. Its hall-mark is genuine openness to and positive probing for spiritual truth and beauty wherever these are to be found. In other words, this new spirit bespeaks a profoundly catholic attitude.